Suture techniques in the surgical management of flexor tendon, Achilles tendon and cruciate ligament injuries: a systematic review - Guoshuai Liu; Gege Lv; Fei Liu (BMC Musculoskeletal Disorders)
Abstract Objective To provide clinicians with reliable recommendations for the selection of appropriate suturing techniques for surgical management of common musculoskeletal soft tissue injuries. Methods A systematic search of PubMed, Springer, Web Science, Vip Database, China National Knowledge, and Wanfang Data for in vitro biomechanical studies on suture techniques in the surgical treatment of musculoskeletal soft tissue injuries covering relevant studies from April 2009 to April 2024 was performed. A generalized classification was made based on the characteristics of the techniques, and recommendations for the selection of suture techniques were made according to the GRADE concept. Results The search strategy returned 1015 articles, of which 66 were included. These studies presented moderate and high levels of evidence-based evidence and provided varying recommendations for the choice of suturing techniques in the treatment of three common musculoskeletal soft tissue injuries. Categorizing suturing techniques according to their structural principles further increases the reliability of opinions. Conclusion The ideal suture technique must be a compromise between the complexity and strength of the repair, which is a great challenge for clinicians. This review can provide an objective and reliable clinical guide for making suture technique choices for common musculoskeletal soft tissue repair.